Transcriptomics and starch biosynthesis analysis in leaves and developing seeds of mung bean provide a basis for genetic engineering of starch composition and seed quality - Umnajkitikorn, Kamolchanok; Boonchuen, Pakpoom; Senavongse, Rattanavalee; Tongta, Sunanta; Tian, Yu; Hu, Yaqi; Petersen, Bent Larsen; Blennow, Andreas (Frontiers in Plant Science, 2024)
Mung bean starch is distinguished by its exceptional high amylose content andregulation of starch biosynthesis in leaves and storage tissues, such as seeds, share considerable similarities. Genetic engineering of starch composition and content, requires detailed knowledge of starch biosynthetic gene expression and enzymatic regulation. In this study we applied detailed transcriptomic analyses to unravel the global differential gene expression patterns in mung bean leaves and in seeds during various stages of development. The objective was to identify candidate genes and regulatory mechanisms that may enable generation of desirable seed qualities through the use of genetic engineering. Notable differences in gene expression, in particular low expression of the Protein Targeting to Starch (PTST) (LOC106758029), starch synthase (SS) 3 (LOC106775746), and starch branching enzyme1 (SBE1) (LOC106762405) encoding genes in developing seeds as compared to leaves were evident. These differences were related to starch molecular structures and granule morphologies. Specifically, the starch molecular size distribution at different stages of seed development correlated with the starch biosynthesis gene expression of the SBE1, SS1 (LOC106774409), granule-bound starch synthases (GBSS) (LOC106771165 and LOC106759330) and isoamylase 1 (ISA1) (LOC106769258) encoding genes. Furthermore, putative hormonal and redox controlled regulation were observed, which may be explained by abscisic acid (ABA) and indole-3-acetic acid (IAA) induced signal transduction, and redox regulation of ferredoxins and thioredoxins, respectively. The morphology of starch granules in leaves and developing seeds were clearly distinguishable and could be correlated to differential expression of Research article SS1. Here, we present a first comprehensive transcriptomic dataset of developing mung bean seeds, and combined these findings may enable generation of genetic engineering strategies of for example starch biosynthetic genes for increasing starch levels in seeds and constitute a valuable toolkit for improving mung bean seed quality.